ANALISIS KESALAHAN BERBAHASA DALAM MORFOLOGI PADA SISWA SEKOLAH DASAR - Agung Setia Pratama; Mita Domi Fella Henanggil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language errors are still commonly found in Indonesian language learning atthe elementary school level, especially in the field of morphology. This study aims todescribe the forms of morphological language errors made by elementary schoolstudents and the factors causing these errors. This research used a descriptivequalitative method with data sources in the form of students’ essays. Data collectiontechniques were carried out through observation, documentation, and note-takingtechniques. The data analysis technique was conducted by identifying, classifying,and describing morphological errors found in students’ writings. The results showedthat the most dominant morphological errors included errors in affixation, prepositionwriting, the use of standard words, and reduplication. These errors were influencedby several factors, such as the influence of regional languages, students’ lack ofunderstanding of Indonesian language rules, lack of writing practice, and the habitof using non-standard language in daily communication. Based on the results of thestudy, it can be concluded that elementary school students’ morphological abilitiesstill need to be improved through more effective Indonesian language learning andthe use of interesting learning media. This study is expected to become a referencefor teachers and future researchers in improving elementary school students’language skills.